2018
DOI: 10.1177/2325967118760815
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Strand Hamstring Autograft Achieves Outcomes Comparable to Those of a 4-Strand Hamstring Autograft With a Graft Diameter of 8 mm or More in Anterior Cruciate Ligament Reconstruction

Abstract: Background:Quadrupled (4-strand) hamstring tendon autografts are commonly used in anterior cruciate ligament (ACL) reconstruction, but there is significant variability in their diameter. The 5-strand hamstring autograft has been used as a means of increasing the graft diameter in patients with undersized hamstring grafts.Purpose:To report the outcomes of primary ACL reconstruction using 5-strand hamstring autografts in patients in whom the 4-strand configuration produced a graft diameter of <8 mm and to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 19 publications
0
58
2
Order By: Relevance
“…Despite significantly larger grafts in the five-strand group (9.06 vs. 8.13 mm), they failed to demonstrate a significant difference in clinical outcomes between groups. 16 Conversely, these data demonstrate a significantly smaller increase than a recently published randomized clinical trial that reported an increase of 1.4 mm (AE0.3 mm) in graft size in a five-strand configuration. 15 Moreover, these data also differ from a separate retrospective study in which the authors compared groups of patients who underwent ALCR using either a five-or four-strand configuration.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…Despite significantly larger grafts in the five-strand group (9.06 vs. 8.13 mm), they failed to demonstrate a significant difference in clinical outcomes between groups. 16 Conversely, these data demonstrate a significantly smaller increase than a recently published randomized clinical trial that reported an increase of 1.4 mm (AE0.3 mm) in graft size in a five-strand configuration. 15 Moreover, these data also differ from a separate retrospective study in which the authors compared groups of patients who underwent ALCR using either a five-or four-strand configuration.…”
Section: Discussioncontrasting
confidence: 63%
“…In fact, despite the increase in graft size in a five-strand configuration in previous studies, none of the authors could demonstrate a statistically significant difference in clinical outcomes and/or re-rupture rates between groups. 4,15,16 When comparing hamstring graft size without controlling for different configurations, Conte et al demonstrated that a graft diameter of 8 mm was associated with a 6.8 times higher relative risk of future graft failure. 5 This systematic review also supports previous observational studies demonstrating that decreased hamstring autograft size is associated with early revision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations